SUSUNAN NAMA SURAT AL-QUR’AN DALAM NAẒAM IBRĀHĪMIYAH KARYA DURAID IBRAHIM AL-MUṢALI - siti hajidah (Al-Fath, 2022)
The Quran consists of a compilation of verses and chapters. Each chapter of the Quran is given a specific name as an identifier. The naming of the chapters follows the sequence in the Mushaf, totaling 114 chapters beginning from Al-Fatihah to An-Nas, facilitating memorization and study. One study that emphasizes the names of these chapters is conducted using Nazam Ibrāhīmiyah. This research delves into the arrangement and names of the chapters found in Nazam Ibrāhīmiyah, which are written differently from their original names to conform to the system and the variety of chapter names based on whether they are tauqifi or ijtihadi. In this study, the author employs a qualitative research method using library research. The findings of this research indicate that the arrangement of chapters in Nazam Ibrāhīmiyah is based on tauqifi, aligning with the Uthmani Mushaf and beginning from Al-Fātiḥah to An-Nās. As for the naming of the chapters, the majority adhere to tauqifi principles, while some exhibit an ijtihadi approach. Nazam Ibrāhīmiyah facilitates Quran memorizers and scholars in quickly and accurately memorizing the names of the Quranic chapters based on the Mushaf's arrangement in 15 verses.